English Instructional Video Design for Islamic Junior High School - Rifqi Aulia Erlangga; Izzati Shaima Shamsudin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
The purpose of this study is to investigate the perceptions of teachers andstudents in Islamic Junior High School about duration, their involvement inthe video (cast), format and post-video watch activities of English supplementary videos to ensure the videos that will be made are effective. Using a descriptive quantitative method, this study reveals that video is a fun learning tool to study English, so that the students don’t mind if the video duration is more than 15 minutes. About the cast, the students inclined to be involved in producing the video. About the format, the majority chooses the drama method with Bahasa subtitled. About the post-video watch activities, they prefer to do a writing rather than a speaking activity. During the video playing, they didn’t taking a note or observing the whole plot yet, so that they wish the video can be replayed outside the class,just like on television or youtube